1989
DOI: 10.1128/mcb.9.6.2445
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and stability of chromosomal DNA coamplified with the CAD gene.

Abstract: We have compared clones of Syrian hamster cells selected for the first amplification of the CAD gene with clones selected for further amplification. The large domain amplified initially was not reamplified as an intact unit. Instead, subregions were reamplified preferentially, and parts of the initial array were often lost. These events reduced the average amount of coamplified DNA accompanying each copy of the selected gene. The degree of amplification was small in the first step (about three extra copies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 29 publications
(30 reference statements)
1
26
1
Order By: Relevance
“…The NotI digestion patterns indicate that DMs do not undergo any detectable rearrangements during this process despite the months of growth in the presence of toxic levels of the DNA-damaging agent MTX. This finding is quite different from the observation in drug-resistant hamster cells containing HSRs that the DNA undergoes complex rearrangements (17,24). Fig.…”
Section: Resultscontrasting
confidence: 55%
“…The NotI digestion patterns indicate that DMs do not undergo any detectable rearrangements during this process despite the months of growth in the presence of toxic levels of the DNA-damaging agent MTX. This finding is quite different from the observation in drug-resistant hamster cells containing HSRs that the DNA undergoes complex rearrangements (17,24). Fig.…”
Section: Resultscontrasting
confidence: 55%
“…A third mechanism, recombination within a replication intermediate (see Wahl 1989), does not directly predict chromosome breakage, heterogeneous deletions from a single parental cell, or vast differences in amplicon sizes. Finally, it has been proposed that the initial amplification intermediates are very large, intrachromosomal, and highly unstable, and they decrease in size over time (Saito et al 1989). This model requires that multiple, typically rare recombination events would have to occur every few cell divisions to account for the observed copy number heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that chromosomal amplicons might be unstable and capable of generating copy number heterogeneity (e.g., see Saito et al 1989). We tested this possibility by isolating six subclones from P75-20 (referred to as P75-20S5 to P75-20S10), which contained the major classes of chromosomally amplified DHFR genes.…”
Section: -20mentioning
confidence: 99%
See 1 more Smart Citation
“…These are paired acentric circular structures called (double) minute chromosomes (DMs) and expanded chromosomal regions (ECRs). Several recent studies indicate that DMs can originate from submicroscopic circular elements called episomes (5,6,37,40,50); however, in some cases, DMs may be generated without such precursors by a process which involves chromosome fragmentation (44). Studies with various genes in different cell lines suggest, and in one case directly show, that DMs integrate into a chromosome to form an ECR (5,7,28,47,49,50; this study).…”
mentioning
confidence: 99%